2021
DOI: 10.1111/zph.12894
|View full text |Cite
|
Sign up to set email alerts
|

Giardia duodenalis in colony stray cats from Italy

Abstract: Giardia duodenalis is the most common intestinal protozoan in humans and animals worldwide, including eight morphologically identical assemblages, infecting pets, livestock, wildlife and human beings. Assemblages A and B are those with the higher zoonotic potential, and they have been detected in several mammals other than humans; the others (C to H) show a higher host specificity. Cats can harbour both the specific Assemblage F and the zoonotic ones A and B. Several studies have been carried out on G. duodena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
2
5
0
1
Order By: Relevance
“…The presence of assemblage A raises the concern of zoonotic transmission due to the association with the presence of clinical signs of the disease [ 13 ]. This coincides with other reports in which the zoonotic assemblages dominated in the cat population [ 24 , 63 , 64 , 65 ]; in contrast, some studies have detected cat-specific assemblage (F) at a higher frequency [ 66 , 67 , 68 ]. Here, further genetic characterization showed that assemblage AII was present at a higher proportion (57%) than assemblage AI (42%), coinciding with Procesi et al [ 63 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The presence of assemblage A raises the concern of zoonotic transmission due to the association with the presence of clinical signs of the disease [ 13 ]. This coincides with other reports in which the zoonotic assemblages dominated in the cat population [ 24 , 63 , 64 , 65 ]; in contrast, some studies have detected cat-specific assemblage (F) at a higher frequency [ 66 , 67 , 68 ]. Here, further genetic characterization showed that assemblage AII was present at a higher proportion (57%) than assemblage AI (42%), coinciding with Procesi et al [ 63 ].…”
Section: Discussionsupporting
confidence: 91%
“…This coincides with other reports in which the zoonotic assemblages dominated in the cat population [ 24 , 63 , 64 , 65 ]; in contrast, some studies have detected cat-specific assemblage (F) at a higher frequency [ 66 , 67 , 68 ]. Here, further genetic characterization showed that assemblage AII was present at a higher proportion (57%) than assemblage AI (42%), coinciding with Procesi et al [ 63 ]. Because AII is predominantly present in humans and is associated with virulence factors that may trigger clinical manifestations, this finding raises the concern for zoonotic transmission [ 69 , 70 ].…”
Section: Discussionsupporting
confidence: 91%
“…A homology search was conducted using the Basic Local Alignment Search Tool available at the National Center for Biotechnology Information (NCBI, http://www.ncbi.nlm.nih.gov) and the BioEdit program, version 7.2. The results were compared with data obtained from the GenBank and the ExPASY program (SIB Swiss Institute of Bioinformatics, Switzerland) available on the NCBI website [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Es ist davon auszugehen, dass 8-30 % der mit Giardien infizierten Tiere von zoonotischen Genotypen betroffen sind [13,23]. Mischinfektionen mit verschiedenen Assemblages können vorgefunden werden [13,24,25].…”
Section: Taxonomieunclassified